Rebranding of freeport A’Famosa outlet / Ainnin Sofiya Rosli and Zahara Ramli - Rosli, Ainnin Sofiya; Ramli, Zahara (Kolej Pengajian Seni Kreatif (KPSK) UiTM Cawangan Melaka, 2023)
Freeport A’Famosa Outlet is a collaboration with London based Freeport Retail, a global manager and investor in the outlet industry, and was opened on 28 January 2016 by Datuk Seri Utama Dr. Ahmad Zahid Bin Hamidi, Malaysia's former Deputy Prime Minister, and Datuk Seri Ir. Haji Idris Bin Haji Haron, Melaka's former Chief Minister. A famous Australian architect created the Dutch heritage design in collaboration with the state government of Melaka. The richly greened landscape, designed as an open-air mall, contains five water features, a lake, four parks and lawns, a windmill, and a carousel. Freeport A’Famosa Outlet was chosen as my final year project after I visited the place for the first time in 2022. I decided upon it because it is one of the main attractions in Melaka. It also has a lot of potential that can be developed to be an outlet that is famous among the tourist and Malaysian citizen rather than its competitors. The purpose of this project is to develop a fresh image that is suitable for the outlet and making it a worldwide design. The plan for this project is to rebrand in practically every aspect, including the logo, tagline, signs, uniforms, livery, counters, and others.